Exports and economic growth in Sub-Saharan Africa: New insights from innovative econometric methods - Furuoka, Fumitaka (Taylor & Francis, 2018)
This study examined the relationship between exports and economic growth in Sub-Saharan Africa. It employed innovative econometric methods, including the Fourier ADF with structural break test, a comparative analysis of three causality tests and a rolling causality test procedure. The findings suggested that there was a statistically significant relationship between exports and economic growth in several Sub-Saharan countries. However, the causal linkages between exports and economic growth in these countries were found to be weak and unstable. These empirical results have some notable policy implications.